2005
DOI: 10.1002/jcp.20549
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of VCAM‐1 expression by tumor necrosis factor‐α in human tracheal smooth muscle cells: Involvement of MAPKs, NF‐κB, p300, and histone acetylation

Abstract: Tumor necrosis factor-alpha (TNF-alpha) has been shown to induce the expression of adhesion molecules in airway resident cells and contribute to inflammatory responses. Here, the roles of mitogen-activated protein kinases (MAPKs) and NF-kappaB in TNF-alpha-induced expression of vascular cell adhesion molecule (VCAM)-1 were investigated in human tracheal smooth muscle cells (HTSMCs). TNF-alpha-enhanced expression of VCAM-1 protein and mRNA as well as phosphorylation of p42/p44 MAPK, p38, and JNK were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
76
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 51 publications
13
76
0
1
Order By: Relevance
“…The cDNA obtained from 0.5 g total RNA was used as a template for PCR amplification as previously described. 17 The primers used were as follows: 5Ј-GGAACCTTGCAGCT-TACAGTGACAGAGCTCCC-3Ј (sense) and 5Ј-CAAGT-CTACATATCACCCAAG-3Ј (anti-sense) for VCAM-1; 5Ј-CAAGGGGAGGTC-ACCCGCGAGGTG-3Ј (sense) and 5Ј-TGCAGTGCCCATTATGACTG-3Ј (anti-sense) for ICAM-1.…”
Section: Reverse Transcription-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA obtained from 0.5 g total RNA was used as a template for PCR amplification as previously described. 17 The primers used were as follows: 5Ј-GGAACCTTGCAGCT-TACAGTGACAGAGCTCCC-3Ј (sense) and 5Ј-CAAGT-CTACATATCACCCAAG-3Ј (anti-sense) for VCAM-1; 5Ј-CAAGGGGAGGTC-ACCCGCGAGGTG-3Ј (sense) and 5Ј-TGCAGTGCCCATTATGACTG-3Ј (anti-sense) for ICAM-1.…”
Section: Reverse Transcription-pcr Analysismentioning
confidence: 99%
“…ICAM-1-luc or VCAM-1-luc activity was determined as previously described using a luciferase assay system (Promega, Madison, WI). 17 …”
Section: Measurement Of Icam-1 and Vcam-1 Luciferase Activitymentioning
confidence: 99%
“…Similarly, VCAM‐1 contributes to macrophage accumulation in developing lesions 61. The reduction in MCP‐1 and VCAM‐1 expression is most likely the consequence of reduced T cell and macrophage activation; macrophage and T cell‐derived cytokines are reduced by RMT1‐10 treatment and tumor necrosis factorα, IL‐6 and IL‐1β are potent inducers of MCP‐1 expression,62, 63, 64 whilst tumor necrosis factor‐α and IL‐1β are also known to induce VCAM‐1 expression 65, 66…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that inflammatory responses following exposure to cytokines are highly dependent on activation of NF-κB, which plays an important role in expression of several inflammatory genes (4,24,25). Previous studies also demonstrated that activation of NF-κB is essential for expression of VCAM-1 induced by TNF-α in human tracheal smooth muscle cells (20). Besides, VCAM-1 promoters contain NF-κB binding sites, which are regulated through MAPKs in several cell types (26).…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1 was not expressed on resting vascular endothelium, but was rapidly induced in response to a number of inflammatory stimuli, consistent with our observation that VCAM-1 expression was maintained at a low level and 700, 1,000, 1,400 µM MSU induced a dose-and time-dependent increase of VCAM-1 expression. Expression of VCAM-1 has been reported to be highly regulated by MAPKs and NF-κB (20)(21)(22). To find out signaling pathways that mediate increased VCAM-1 expression in human synovial cells, we performed Western blotting to examine the activation of several signaling molecules including 3 MAPKs (ERK1/2, p38 MAPK, and JNK), and PPARγ.…”
Section: Discussionmentioning
confidence: 99%